HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENCEGAHAN COVID-19 PADA SISWA DI SMK NEGERI I GEDANGSARI - Erlina Hermawati (STIKES DUTAGAMA KLATEN, 2021)
Background: The Covid-19 outbreak started in Wuhan in December 2019, until it finally spread to the world. So far, many people have died as a result of being confirmed positive for COVID-19. Students are one part of the community that has been affected by the Covid-19 outbreak. Knowledge of Covid-19 prevention efforts is very important for students so that students are expected to be able to behave appropriately in order to break the chain of transmission of Covid-19. Objective: To determine the relationship between knowledge and Covid-19 prevention behavior in students at SMK Negeri I Gedangsari. Methods: This research is a quantitative study with a correlation analytic design. The sampling technique is total sampling. The sample who is willing to become a respondent and fill out the link https://forms.gle/JV98ok5ArNGxdiYc7 is 76 respondents. Data were analyzed using Kendall Tau correlation analysis. Research Results: The majority of respondents' gender is female with an average age of 17 years. The majority of Covid-19 prevention knowledge is good and Covid-19 prevention behavior is quite good. The results of the Kendall Tau correlation test show a p value of 0.00 < 0.05, which indicates that there is a relationship between knowledge and Covid-19 prevention behavior in students. Conclusion: There is a relationship between knowledge and the behavior of Covid-19 prevention efforts in SMK Negeri I Gedangsari students, with a positive relationship direction. Keywords: Knowledge, Covid-19 Prevention Behavior, Students